Accelerated Intermittent Theta Burst Stimulation in Smoking Cessation: Placebo Effects Equal to Active Stimulation When Using Advanced Placebo Coil Technology - Mikellides, Georgios; Michael, Panayiota; Psalta, Lilia; Stefani, Artemis; Schuhmann, Teresa; Sack, Alexander T. (Frontiers in Psychiatry, 2022)
Smoking is currently one of the main public health problems. Smoking cessation is known to be difficult for most smokers because of nicotine dependence. Repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (DLPFC) has been shown to be effective in the reduction of nicotine craving and cigarette consumption. Here, we evaluated the efficacy of accelerated intermittent theta burst stimulation (aiTBS) (4 sessions per day for 5 consecutive days) over the left DLPFC in smoking cessation, and we investigated whether the exposure to smoking-related cues compared to neutral cues during transcranial magnetic stimulation (TMS) impacts treatment outcome. Α double-blind, randomized, controlled study was conducted in which eighty- nine participants (60 males and 29 females; age 45.62 ± 13.42 years) were randomly divided into three groups: the first group received active aiTBS stimulation while watching neutral videos, the second group received active aiTBS stimulation while watching smoking-related videos and the last group received sham stimulation while watching smoking-related videos. Our results suggest that aiTBS is a tolerable treatment. All treatment groups equally reduced cigarette consumption, nicotine dependence, craving and perceived stress. The effect on nicotine dependence, general craving and perceived stress lasted for at least one week after the end of treatment. Active aiTBS over the left DLPFC, combined with smoking related cues, is as effective as active aiTBS combined with neutral cues as well as placebo aiTBS in smoking cessation. These findings extend the results of previous studies indicating that TMS therapy is associated with considerably large placebo effects and that these placebo effects may be further increased when using advanced placebo coil technology.